Evolution of Indirect Restorations for Fixed Prosthodontics: Planning, Preparation and Cementation. Issue 3 (September 2019) - Patel, Mahul
The provision of indirect restorations utilising contemporary materials for single or multiple abutment units in primary health care is an essential requirement for all general dental practitioners to ensure predictable patient outcomes. This paper highlights the important considerations for comprehensive planning and adept treatment execution and delivery that can enhance the patient's dental experience and outcome. A selection of clinical cases highlighting established and novel restorative materials utilising conventional and adhesive clinical techniques is presented and discussed.